1998
DOI: 10.1128/aac.42.3.682
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Antimalarial Drug Activity, Accumulation, and Inhibition of Heme Polymerization in Plasmodium falciparum In Vitro

Abstract: We have investigated the contribution of drug accumulation and inhibition of heme polymerization to the in vitro activities of a series of antimalarial drugs. Only those compounds exhibiting structural relatedness to the quinolines inhibited heme polymerization. We could find no direct correlation between in vitro activity against chloroquine-susceptible or chloroquine-resistant isolates and either inhibition of heme polymerization or cellular drug accumulation for the drugs studied. However, in vitro activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
167
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(175 citation statements)
references
References 25 publications
8
167
0
Order By: Relevance
“…4f) was also studied, and revealed that it has a fit value of 5.85 and lacks only the PI feature at the correct location. From these observations it can be assumed that the RA feature may be essential but not sufficient for a a Data for activities against chloroquine sensitive (3D7) of P. falciparum are from (Hawley et al, 1998) b Activity scale: +++ (0-50 nM, highly active), ++ (51-200 nM, moderately active), + ([200 nM, poorly active) molecule to be antimalarial by targeting haem detoxification pathway. Some reports in the literature emphasize that chloroquine and other quinoline molecules inhibit haem polymerization by forming a p-p stack complex (Egan and Marques, 1999;Egan et al, 1997) but the X-ray crystallographic structures of the resulting complexes have not yet been reported.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…4f) was also studied, and revealed that it has a fit value of 5.85 and lacks only the PI feature at the correct location. From these observations it can be assumed that the RA feature may be essential but not sufficient for a a Data for activities against chloroquine sensitive (3D7) of P. falciparum are from (Hawley et al, 1998) b Activity scale: +++ (0-50 nM, highly active), ++ (51-200 nM, moderately active), + ([200 nM, poorly active) molecule to be antimalarial by targeting haem detoxification pathway. Some reports in the literature emphasize that chloroquine and other quinoline molecules inhibit haem polymerization by forming a p-p stack complex (Egan and Marques, 1999;Egan et al, 1997) but the X-ray crystallographic structures of the resulting complexes have not yet been reported.…”
Section: Resultsmentioning
confidence: 99%
“…The purpose of these hypotheses is not just to predict the activity of the training-set molecules accurately but also to predict the activity of the test-set molecules and (Hawley et al, 1998) b Activity scale: +++ (0-50 nM, highly active), ++ (51-200 nM, moderately active), + ([200 nM, poorly active) classify them correctly as active or inactive so it can be used as a virtual screening tool to find new antimalarials. We constructed a set of test molecules (Fig.…”
Section: Activity Prediction Of Test-set Moleculesmentioning
confidence: 99%
See 2 more Smart Citations
“…The polymerization process is a mechanism of detoxification and can be targeted for antimalarial therapy (Egan and Marquis, 1999). Considerable data now support the hypothesis that antimalarial quinolines inhibit parasite growth by binding to hematin and preventing its aggregation to hemozoin (Egan and Marques, 1999;Egan et al, 1997;Dorn et al 1998;Hawley et al, 1998). Portela et al (2003) used electrostatic potential calculations and docking studies to explain the mode of interaction of quinoline antimalarials with the receptor hematin which strengthens the nonenzymatic theory of haem detoxification.…”
Section: Introductionmentioning
confidence: 93%